Bedah Anak Dalam Praktek Pelayanan Primer - Shalita Dastamuar (Conferences of Medical Sciences Dies Natalis, 2019)
In primary practice services we sometimes find surgical abnormalities in children. From complaints of lumps in the groin, difficulty defecating (BAB), flatulence, until the tumor. This symposium aims to provide a general description of these cases and how to handle the initial cases of Pediatric Surgery in Primary Service settings.